2010
DOI: 10.1007/s11259-010-9355-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of nitric oxide concentration in plasma and uterine secretes with puerperal endometritis in dairy cows

Abstract: Endometritis is an inflammation of the endometrial lining of the uterus without systemic signs, which is associated with chronic postpartum infection of the uterus with pathogenic bacteria. Nitric oxide (NO) is an inflammatory mediator that among other effects causes smooth muscle relaxation and mediated cytoimmunity and inflammation toxicity. To see if the nitric oxide concentration in plasma and uterine secrets is related with postpartum endometritis, NO concentrations in plasma and uterine secrets were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Li et al reported that uterine tissue from cows with clinical endometritis had high expression of NOS2 mRNA [26]. Our findings also demonstrate that LF significantly reduced the LPS-induced increase in the NO levels in uterine tissue in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 79%
“…Li et al reported that uterine tissue from cows with clinical endometritis had high expression of NOS2 mRNA [26]. Our findings also demonstrate that LF significantly reduced the LPS-induced increase in the NO levels in uterine tissue in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 79%
“…Free radicals lead to changes in NOS levels in endometrium (Alghamdi et al, 2005). In a study conducted by Li et al (2010), it was observed that NO levels were higher in cows suffering from endometritis, in comparison to healthy animals. It was demonstrated that NO increased to higher levels with increased severity of endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NO a by-product of L-arginine (Ozcan and Ogun, 2015) increases in both the uterine discharge and the blood serum (Xue et al, 2015). NO, locally secreted from the ovaries, affects the size and functional phase of the follicle as well as ovulation and development and regression of the corpus luteum (Li et al, 2010;Pande et al, 2013). For rapid uterine involution during the postpartum period, uterine content is required to be expelled.…”
mentioning
confidence: 99%
See 2 more Smart Citations